Bangladesh Rural Advancement Committee audited financial statements December 31, 1999 - BRAC (© BRAC, 2016)
This Financial Statement prepared by Ernst and Young, Public Accountants, Kuala Lumpur, Malaysia and S. F. Ahmed & Co. Chartered Accountants, House # 25, Road # 13A, Block # D, Banani Dhaka- 1213, Bangladesh.